The Sociology of Pandemics: Agenda for a Sociologist in Post-COVID-19 Era - Uzobo, Endurance; Imbazi, Woyengitari (Social Science Research, 2022)
Global outbreak of crises often creates social changes that members of the society are challenged with in terms of adaptation and coping mechanism. However, no doubt the gainsaying that the outbreak of the coronavirus pandemic has created some uprising in society today. Thus, this commentary focuses on some of the pertinent emerging social issues that havearisen after the coronavirus pandemic and the successions of the pandemic waves. This paper believedthat a sociological insight is a vital tool for planning after the COVID-19 crises, alongside medical and logistic expertise. Consequently, looking at the pandemic from just a biomedical perspective will only reveal half of the story as the biomedical will neglect the symbolic dimension of how pandemics become social reality. On this note, this commentary discussedthe important contributions the discipline ofSociology can make in understandingthe global Coronavirus pandemic. In discussing the direct contributions of sociology to COVID-19, the debate in this commentary addressed four(4) key issues namely; (1) uncovering and identifying the social components of the pandemic; (2) observing and examining the manners in which institutional systems and members of society have managed the pandemicoutbreak and its different waves; (3)investigating the level of public trust on Covid-19 protocol measures put in place by government and (4) to analyse the method on how the COVID-19 pandemic is likely to set a new world order.